High systemic inflammation score is associated with adverse survival in skull base chordoma - Li, Mingxuan; Bai, Jiwei; Xiong, Yujia; Shen, Yutao; Wang, Shuai; Li, Chuzhong; Zhang, Yazhuo (Frontiers in Oncology, 2022)
Background: The systemic inflammation score (SIS), based on preoperative lymphocyte to monocyte ratio (LMR) and albumin (ALB), was recently developed and is demonstrated to be a novel prognostic indicator in several cancers. However, data discussing the utility of SIS in chordoma are lacking. We aimed to investigate the distribution and the prognostic role of SIS in primary skull base chordoma patients undergoing surgery. Material and methods: Preoperative SIS was retrospectively collected from 183 skull base chordoma patients between 2008 and 2014 in a single center. Its associations with clinical features and overall survival (OS) were further analyzed. The SIS-based nomogram was developed and evaluated by the concordance index (C-index), time-dependent receiver operating characteristic (ROC) curve, calibration curve, and decision curve analysis (DCA). Results: The numbers of patients in the SIS 2, 1, and 0 group were 29 (15.8%), 60 (32.8%), 94 (51.4%), respectively. High SIS was associated with older age (p = 0.008), brainstem involvement of tumors (p = 0.039), and adverse OS (p < 0.001). Importantly, multivariate Cox analysis showed that high SIS independently predicts adverse OS. Furthermore, the nomogram based on SIS and clinical variables showed eligible performance for OS prediction in both training and validation cohorts. Conclusions: The SIS is a promising, simple prognostic biomarker, and the SIS-based nomogram serves as a potential risk stratification tool for outcome in skull base chordoma patients.